A simple cell proliferation assay and the inflammatory protein content show significant differences in human plasmas from young and old subjects - Muraglia, A.; Utyro, O.; Nardini, M.; Santolini, M.; Ceresa, D.; Agostini, V.; Nencioni, A.; Filaci, G.; Cancedda, R.; Mastrogiacomo, M. (Frontiers in Bioengineering and Biotechnology, 2024)
Some studies showed a "rejuvenating" effect of exposing aging tissues to a young environment. In mice heterochronic parabiosis experiments, in response to the young organism, the old animal lived longer compared to isochrony old age-matched conjoint animals. Comparable "rejuvenating" effects were obtained by injecting young plasma in old mice. This raised great hopes of slowing down the senescence process in humans by injection of young plasma, as well as to prevent or cure age-related diseases. Some clinical trials are currently being performed or recently completed. However, these studies are small and of limited duration and we are still missing convincing evidence to support the effectiveness of young plasma injection. It is urgent to perform additional investigations, including the development of an assay to measure the cell proliferation induction capability of the different human plasmas, before one can seriously think of a large-scale treatment of humans. We adopted a simple method to measure the potential of different plasmas in supporting cell line proliferation regardless of the co-presence of a platelet lysate. By comparing plasmas from young and old subjects we observed a decreased activity in plasmas from old individuals. The young plasma effect may be attributed to specific proteins, and growth factors more abundant in younger individuals that could decrease with age. Alternatively, or at the same time, the reduced cell proliferation support could be due to inhibitors present in the old plasma.To study the different protein content of young and old plasmas was out of scope of this article. Such differences should be adequately investigated by proteomics on many samples. However, a preliminary study of the different protein content of young and old plasmas was part of the assay validation using a commercially available cytokine array for parallel determination of the relative levels of 105 selected human proteins. We could show the existence of specific differences between young and old plasmas and that plasmas from old individuals presented a higher concentration of "inflammatory" proteins.